ENVIRONMENTAL LITERACY ON GARBAGE MANAGEMENT AND GREENING ‎ACTIVITY OF HIGH SCHOOL STUDENTS IN GREEN SCHOOL AND NON-GREEN ‎SCHOOL‎ - Ratri Wulandari; Eka Sulistiyowati (EDUSAINS, 2017)
This survey research was conducted to understand the difference and level of environmental awareness and knowledge on solid waste management dan vegetation re-planting of students from Eco-School (adiwiyata) and Non Eco-School (non-adiwiyata). The number of respondents was 198 students from two high Eco-Schools (SMA N 1 Pengasih and MAN 2 Wates) and two high Non Eco-Schools (SMA N 1 Girimulyo and SMA N 1 Wates). Sample was chosen by random sampling. Students were given a set of questionnaires, which consisted section A tested students awareness and section B tested students knowledge. The data were statistically analysed using Mann-Whitney and descriptive statistics. The results of Mann-Whitney showed that there are significant difference on environmental awareness and knowledge between student taught in Eco-School and student taught in Non Eco-School (Sig.< 0,05). Meanwhile, the level of environmental awareness and knowledge between student taught in Eco-School and student taught in Non Eco-School are in the same level. The level of environmental awareness between student Eco-School and Non Eco-School is in the same low level and the level of environmental knowledge between student Eco-School and Non Eco-School is in the same low level. Keywords: Environmental literacy; Eco School (adiwiyata); solid waste management; vegetation re-planting